Jo Baer - up close in the land of the giants - Baer, Jo 1929-2025 (Pace Gallery, 2020)
This new publication provides deep insight into Baer's research-based approach of locating source imagery in the Irish landscape, which has inspired and informed her visual lexicon for two decades.
Ausstellungsdaten ermittelt: "Jo Baer: The Risen/Originals", Nov 6 - Dec 19, 2020, Pace Gallery, New York
Keywords: Baer, Jo -- 1929-2025; Bildband; Ausstellungskatalog -- Pace Gallery -- 06.11.2020-19.12.2020 -- New York, NY